True phase quantitative susceptibility mapping using continuous single‐point imaging: a feasibility study. Issue 3 (16th October 2018) - Jang, Hyungseok; Lu, Xing; Carl, Michael; Searleman, Adam C.; Jerban, Saeed; Ma, Yajun; von Drygalski, Annette; Chang, Eric Y.; Du, Jiang
Abstract : Purpose: In this study, we explore the feasibility of a new imaging scheme for quantitative susceptibility mapping (QSM): continuous single‐point imaging (CSPI), which uses a pure phase encoding strategy to achieve true phase imaging and improve QSM accuracy. Methods: The proposed CSPI is a modification of conventional SPI to allow acquisition of multiple echoes in a single scan. Immediately following a phase encoding gradient, the free induction decay is continuously sampled with extremely high temporal resolution to obtain k‐space data at a fixed spatial frequency (i.e., at a fixed k‐space coordinate). By having near‐0 readout duration, CSPI results in a true snapshot of the transverse magnetization at each TE. Additionally, parallel imaging with autocalibration is utilized to reduce scan time, and an optional temporal averaging strategy is presented to improve signal‐to‐noise ratio for objects with low proton density or short T2* decay. The reconstructed CSPI images were input to a QSM framework based on morphology enabled dipole inversion. Result: In an experiment performed using iron phantoms, susceptibility estimated using CSPI showed high linearity (R 2 = 0.9948) with iron concentration. Additionally, reconstructed CSPI phase images showed much reduced ringing artifact compared with phase images obtained using a frequency encoding strategy. In an ex vivo experiment performed using human tibia samples, estimated susceptibilities ranged from –1.6 to –2.1 ppm, in agreement with values reported in the literature (ranging from –1.2 to –2.2 ppm). Conclusion: We have demonstrated the feasibility of using CSPI to obtain true phase images for QSM.